ONTOGENESIS. HEREDITARY DISEASES IN CHILD DEVELOPMENT - Abdumuminova Ra’no Narbuvayevna; Maxmudov Kamaliddin Xamidovich; Xojiyeva Laylo Xazratovna (PEDAGOGS, 2024)
Abstract: The skull is the most common layer of the skeleton, which has a cartilage and bone structure that performs the function of support and protection for the brain, organs of vision and hearing, the nucleus, and the primary processing of the digestive and respiratory systems. Brain development begins in the embryonic period. During this period, any multifactors for the mother will lead to the birth of an embryo with genetic diseases in the future.